A critical and speculative review on microRNA technology in crop improvement: Current challenges and future directions. (September 2018) - Zhang, Baohong; Unver, Turgay
Highlights: MicroRNAs have wide application in agriculture. A new nomenclature has been proposed for naming a microRNA. Functional study should be performed for plant miRNA. Genome editing is a new genetic tool for miRNA functional study. Abstract: MicroRNAs (miRNAs) lie at the center of gene regulation and, as such, have become novel targets for crop improvement including the enhancement of crop quality and yields as well as responses to environmental stresses. There are several major issues related to miRNA technology including the functional analysis of miRNAs and their nomenclature. In this critical and speculative review, we recommend several directions for future plant miRNA research and perspectives. Research on miRNA needs to be extended from merely descriptive studies to functional studies. More genetic tools, such as genome editing, should be developed for miRNA functional study. Obtaining transgenic plants is a bottleneck for plant miRNA functional studies and, hence, more reliable transformation methods need to be developed. We also propose a new terminology approach for miRNA nomenclature. The current miRNA nomenclature is confusing and has mislead much research. Here we suggest to name a miRNA as miR#-5p or -3p, and to name their opposite strand as miR#*-3p or -5p. The advantages of the new nomenclature is that it covers information on the history, relationship, family, and location of an individual miRNA. It recognizes both traditional and new discovery.